Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (University of Minnesota Press, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

La haine et l'amour, la boîte noire du féminisme? Une critique de l'éthique du dévouement - Molinier, Pascale (Nouvelles Questions Feministes, 2004)
Les soins étant réalisés majoritairement par des femmes, on tend à considérer l’amour (des malades, des enfants) « naturel » et normal. Or, le travail de soin peut également générer de la haine envers les personnes dépendantes. Celle-ci n’est pas moins normale que l’amour et sa prise en compte modifie l’analyse des situations de soins. Pour l’heure, la haine est occultée dans les traditions savantes, en particulier dans les théories de l’éthique du dévouement, comme dans les témoignages des travailleuses, ainsi que le suggère une enquête réalisée auprès d’auxiliaires de puériculture. Il en résulte un déficit de visibilité du travail qui permet de conjurer la haine et la violence
Keywords: approches et analyses; care; discipline; discours dominant; projet charge mentale; psychologie; ressource en ligne; sciences humaines; sexisme; soins aux enfants; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences